STUDI DESKRIPTIF TENTANG ABDURRAHMAN BIN AUF PROTOTYPE ENTREPRENEUR MUSLIM SUKSES - Putri Apria Ningsih (Imara: JURNAL RISET EKONOMI ISLAM, 2017)
Believed on earth and trusted in the heavens is another name given to Abdurrahman bin Auf,a friend of the Prophet. He was popular because his honesty and generosity in trading, as a result hebecome a rich person. He also has many remarkable stories in his life that can be emulated by people intheir daily life. There is famous hadith about a statement from the Prophet who says that Abdurrahmanbin Auf will enter the heaven by crawling. If he wants to hinder that situation, he must spend all hiswealth in the afternoon. It was one of the reasons why he became famous as a true Muslim entrepreneur